A description of the larva of Mesopodagrion tibetanum australe (Odonata: "Megapodagrionidae"). Issue 4 (1st October 2016) - Yu, Xin
Abstract : The larva of the genus Mesopodagrion was identified with the help of DNA barcoding and described for the first time. The larvae have flat horizontal gills resembling those of Argiolestidae but the adults lack setae on the shaft of the genital ligula. Molecular data are shown to be useful and necessary in larval identification and should be adopted as a standard tool in future studies.